Artificial Intelligence/Machine Learning in Nuclear Medicine and Hybrid Imaging - Veit-Haibach, Patrick; Herrmann, Ken.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book includes detailed explanations of the underlying technologies and concepts used in Artificial Intelligence (AI) and Machine Learning (ML) in the context of nuclear medicine and hybrid imaging. A diverse team of authors, including pioneers in the field and respected experts from leading international institutions, share their insights, opinions and outlooks on this exciting topic. A wide range of clinical applications are discussed, from brain applications to body indications, as well as the applicability of AI and ML for cardio-vascular conditions. The book also considers the potential impact of theranostics. To balance the technology-heavy and disease-specific applications, it also discusses ethical / legal issues, economic realities and the human factor, the physician. Though this discussion is not based on research and outcomes, it provides important insights into the ramifications of how AI and ML could transform Nuclear Medicine and Hybrid Imaging practice. As the first work highlighting the role of these concepts specifically in this field, rather than for medical imaging in general, this book offers a valuable resource for Nuclear Medicine Physicians, Radiologists, Physicists, Medical Imaging Administrators and Nuclear Medicine Technologists alike.
Keywords: Nuclear medicine; Medical informatics; Nuclear Medicine; Health Informatics; Multimodal Imaging; Molecular Imaging; Image Processing, Computer-Assisted